Efektivitas Model Pembelajaran Project Based Learning (PjBL) Terhadap Hasil Belajar Matematika pada Siswa Kelas VII - Maharani Aihunan; Suhartini Sumadi; Mukhlas Triono (Jurnal Inovasi Pendidikan Matematika (JIPM), 2025)
This study aims to determine the effectiveness of the project-based learning model on mathematics learning in class VII MTs at Integral Hidayatullah. This type of research is quantitative, utilizing data collection techniques that include a pre-test and a post-test. The results of this study indicate that the project-based learning model is considered less effective in its application. This is assessed based on the N-Gain test results of 48.3980, or at an N-Gain percent of 48%, with an interpretive comparison of around 40 ≤ g ≤ 55. So, it can be concluded that the effectiveness of the project-based learning model on mathematics learning outcomes in class VII is less effective.